2021
DOI: 10.47432/2021.37.2.2.
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Levels of Bulk Densities Combination on Yield and Yield Component of Wheat (Triticum Aestivum L.)

Abstract: An experiment was conducted on the impact of different levels of bulk densities combination on yield and yield components of wheat. Three bulk density levels 1.00-1.30 (A) g cm-3, 1.30-1.60 (B) g cm-3 and 1.60-1.90 (C) g cm-3 with three different depths (0-15, 16-30 and 31-45 cm) were used in the experiment using silt loam soil (Pedocals). The total treatments were 27 in the experiment with three replications. The experimental design was completely randomized design (CRD). The treatment means were checked at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These results are in accordance with Anjum et al (2018), who reported that various hybrids responded differently for shoot thickness. In contrast, Sabir et al (2021) reported that various hybrids responded differently in shoot thickness, but no effect was due to soil compaction. However, Yan et al (2019) also recorded a significant change in shoot thickness in maize by different bulk densities in soil.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These results are in accordance with Anjum et al (2018), who reported that various hybrids responded differently for shoot thickness. In contrast, Sabir et al (2021) reported that various hybrids responded differently in shoot thickness, but no effect was due to soil compaction. However, Yan et al (2019) also recorded a significant change in shoot thickness in maize by different bulk densities in soil.…”
Section: Discussionmentioning
confidence: 93%
“…The statistical software SAS (SAS Institute Inc) was used to analyze data. This analysis of variance provided the standard error difference and the application of Fisher's tests for comparing treatments (Sabir et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation